Pengaruh Model Pembelajaran Terhadap Hasil Belajar Siswa pada Materi Pencemaran Lingkungan di SMA Negeri 1 Bendahara Aceh Tamiang - Fauzi Fauzi; Binari Manurung; Syahmi Edi (Jurnal Pendidikan Biologi, 2016)
This research aim to investigate the effect of learning model to students learning outcomes in environmental pollution subject matter. This research method was quasi experimental design with pretest and posttest control group design. Research population in this research was the whole Grade X students in SMA Negeri 1 Bendahara academic year 2015/2016 as much as 120 students. Samples of this research were 3 regular classes of Grade X with total 90 students. Samples of this research were choosen based on special criteria (purpossive sampling). Data were collected using test instrument. Data analysis technique was using analysis of covarians. The result of study showed that there was a significant effect of learning models (project and problem based learning) to students outcome. (Fcount = 16,46; P = 0,00). Based on this study result, it can be concluded that students outcome which taught using project based learning model was higher than problem based learning and convensional learning models.